Home-based long-term physical endurance and inspiratory muscle training in children and adults with Fontan circulation - Walzer, Lena; Sallmon, Hannes; Kelm, Marcus; Dirks, Stefan; Meyer, Michael; Kramer, Peter; Wolfarth, Bernd; Thouet, Thomas; Ovroutski, Stanislav; Berger, Felix; Schleiger, Anastasia (Frontiers in Cardiovascular Medicine, 2024)
Background and study aim Regular physical activity is highly recommended for patients with Fontan hemodynamics. Our aim was to investigate the effects of a long-term individualized home-based endurance training (IHET) on a bicycle ergometer in combination with inspiratory muscle training (IMT) in pediatric and adult patients after Fontan palliation. Additionally, factors influencing the trainability of Fontan palliated patients were analyzed. Methods From 2018 to 2021 a single-center prospective study was performed initially including 25 Fontan palliated patients. During study period nine patients were excluded due to incompliance. A Magbike® bicycle ergometer (DKN Technology, France) was used for IHET and a POWERbreathe® Medic plus device (HaB GmbH, Germany) was utilized for the IMT. Over the study period, bike training was increased from 90 min of basic endurance training per week to additional 25 min of interval training per week. IMT consisted of 30 breaths per day for 6–7 days per week with pressure adaption over time. Patients underwent cardiopulmonary exercise testing (CPET) and body plethysmography including measurement of respiratory muscle strength at baseline and at follow-up examinations at 4, 10 and 22 months. Results Follow-up examinations were completed by 18/25 patients (72.0%) at 4 and 10 months and 16/25 patients (64.0%) at 22 months. Median exercise capacity slightly increased by 0.13 W/kg from baseline to last follow-up (p = 0.055, 95%CI: 0.0–0.36). However, a significant increase of oxygen pulse of 0.7 ml/beat (p = 0.006, 95%CI: 0.38–2.22) was detectable. IMT significantly improved respiratory function with an increase of inspiratory vital capacity (VCin/reference) by 4.0% (p = 0.016, 95%CI: 0.8–8). Median maximal inspiratory pressure increased by 1.2 kPa (p = 0.003, 95%CI: 0.64–3.19) and expiratory pressure by 1.5 kPa (p = 0.036, 95%CI: 0.08–2.29). No adverse events or unplanned interventions occurred during the study. Patients' subjective quality of life did not significantly change over the study period. Conclusion In Fontan palliated patients, IHET in combination with IMT leads to a significant increase in oxygen pulse, inspiratory vital capacity as well as median maximal inspiratory and expiratory pressure but not to significant improvement of quality of life. Fontan patients should be encouraged to perform regular home-based exercise training.